Pengaruh Promosi Islami Terhadap Keputusan Nasabah Memilih Produk Tabungan Emas Di Unit Pegdaian Syariah JMP Surabaya - Sari, Novita; Fikriyah, Khusnul (Jurnal Ekonomika dan Bisnis Islam, 2021)
AbstractThis study aims to determine the effect of Islamic promotion on customer decisions to choose gold savings products at UPS JMP Surabaya. This research uses a quantitative approach with descriptive methods. Researchers used the interview method and used a questionnaire to collect data. And involving 84 respondents who have been tested for validity and reliability. So the results of the simple linear regression test and the results of the t test show if Islamic promotion have an effect on customer decision in choosing gold savings products. It is hoped that the next researchers who take a similar theme, researchers hope to add new variables so that they can provide various kinds of information related to the effect of Islamic promotion on customer decisions in choosing gold savings products, or can expand the subject of this study.Keywords: Customer Decisions, Promotion, Gold Savings